Septic shock with dermatitis and necrotizing myositis due to Vibrio vulnificus infection (Case report) - Trinh, Van Thong; Tran, Van Thanh; Nguyen, Ngoc Son; Nguyen, Viet Thanh; Hoang, Van Chau (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Vibrio vulnificus (V. vulnificus) is a gram-negative bacterium that can cause serious, potentially fatal infections. V. vulnificus causes three distinct syndromes: Overwhelming primary septicemia caused by consuming contaminated seafood, wound infections acquired when an open wound is exposed to contaminated warm seawater, and gastrointestinal tract-limited infections. Case-fatality rates are higher than 50% for primary septicemia, and death typically occurs within 72 hours of hospitalization. Risk factors for V. vulnificus infection include chronic liver disease, alcoholism, and hematological disorders. When V. vulnificus infection is suspected, appropriate antibiotic treatment and surgical interventions should be performed immediately. Third-generation cephalosporin with doxycycline, or quinolone with or without third-generation cephalosporin, may be potential treatment options for patients with V. vulnificus infection.